ETHNOCULTURAL LINGUISTIC EXPRESSIONS IN LYRIC-EPIC POETRY (BASED ON THE EXAMPLE OF THE POEM KOZY KORPESH-BAYAN SULU) (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2026)
This article investigates the characteristics and cognitive significance of ethnocultural expressions within the lyric-epic poem Kozy Korpesh-Bayan Sulu, recognized as a shared cultural heritage of the Turkic peoples. The study emphasizes the poem’s distinctive position in the nation’s literary history as one of the earliest examples of lyric-epic poetry. The primary objective is to analyze the linguistic features of the Zhanak version of the poem, which encapsulate the cultural values and lifestyle of the Kazakh people, while underscoring the cumulative function of language as a repository of cultural knowledge. The authors classify and systematically analyze ethnocultural units into four semantic categories: 1) terms associated with customs and traditions, 2) toponyms, 3) anthroponyms, and 4) designations of household items, including clothing, jewelry, weapons, and utensils. Through this analysis, the study identifies key ethnocultural elements that embody the spiritual and material culture of the nation and delineates their functional domains. The research reveals the pivotal role of the lyric-epic poem in reflecting the essence of the Kazakh language and fostering national identity. Methodologically, the study employs comparative, lexical-semantic, and etymological approaches, among others. The findings demonstrate that many ethnocultural lexical units in the analyzed version of the poem retain their relevance in contemporary linguistic usage. Furthermore, the etymology of certain archaic terms is explored, shedding light on their obsolescence and their integration into the lexical-semantic system of the Kazakh language. This article is intended for philologists and scholars with an interest in the Kazakh language and culture. Its results also provide valuable material for academic courses such as Lexicology and Phraseology, Linguoculturology, Linguistic Analysis of Literary Texts, and Oral Folk Literature.